IPCC-BASED HOUSEHOLD CLIMATE VULNERABILITY INDEX IN SALOKARAJA VILLAGE, SOUTH SULAWESI - Rusdi Rusdi; Helmi Ayuradi Miharja; Inaz Armadani; Arfandi Arfandi; Darma Jaya Syahruddin (USN Kolaka, 2025)
Climate change is intensifying floods and droughts across rural Indonesia, yet vulnerability assessments rarely drill down to the village scale. This study evaluates household-level vulnerability in Salokaraja Village, Soppeng Regency, through the IPCC framework of exposure, sensitivity, and adaptive capacity. Primary data were gathered via a survey of 115 households, key-informant interviews, and focus-group discussions; long-term rainfall records (2000-2023), disaster reports, and a 30-m DEM provided secondary inputs. Indicators were normalised, weighted, and combined into a composite index, then analysed statistically and mapped using GIS interpolation. Results reveal that 34 % of households are highly vulnerable, with an average index score of 0.55; flood-plain exposure and rice-monoculture dependence drive risk, while adaptive capacity—particularly credit access (27 %) and climate-information literacy (46 %)—shows a strong negative relationship with vulnerability (? = –0.44). Policy recommendations include rehabilitating tertiary irrigation and flood canals, integrating BMKG seasonal outlooks into extension services, offering subsidised